Perlindungan Hukum Terhadap Pekerja Akibat Pemutusan Hubungan Kerja Dimasa Pandemi Covid-19 - Fitrah Agung Sabda Pamungkas; Anang Dony Irawan (Ajudikasi : Jurnal Ilmu Hukum, 2021)
Covid-19 significantly affected nearly all companies in which many were forced to discontinue the working relationship against excuse of force majeure, proper action was required to protect the rights of worker so that a center point could be avoided the decision of termination if the working relation ship. This assessment uses the nomadic yuidis method of judging where it will use law approaches and several sources such as books, journal and others. According to public opinion, government are obligated to reserve human rights against workers in order to keep economy in society.It is vital that prevention against layoffs be made to reduce Indonesia’s unemployment rate, there is also the right of the workers to make the best contributions to boost productivity and turnover to the company. The government is expected to provide better jobs as well as relevant competency programs for reducing Indonesia’s unemployment rates.